Impact of socioeconomic, demographic, maternal, infant and healthcare factors on early initiation of breastfeeding in Bangladesh: Evidence from Bangladesh demographic health survey (BDHS) 2022 data - Nihar Ranjan Sikder; Bijoy Rajbongshi; Monir Hosen; Md. Mohibul Nasir Sopon; Afsana Mimi (PLoS ONE, 2026)
Background Introducing an infant to the breast within an hour of birth is known as early initiation of breastfeeding (EIBF). Early initiation of breastfeeding (EIBF) was measured using BDHS 2022 data and defined as initiation of breastfeeding within one hour of birth, based on maternal self-report of the time elapsed between delivery and first breastfeeding. Using maternal self-reported timing of first breastfeeding from the Bangladesh Demographic and Health Survey (BDHS) 2022, this study examined factors associated with EIBF among mothers in Bangladesh. Methods Data from 4,758 women who were fertile and had given birth were included in the study. To investigate the prevalence of EIBF and its association with different factors (socioeconomic, demographic, maternal, infant, and healthcare-related), descriptive analysis, and bivariate analysis using Pearson chi-square tests were carried out. Significant EIBF factors were found using binary logistic regression analysis. Results Skin-to-skin contact within one hour of birth was significantly associated with higher odds of EIBF (OR = 1.62; 95% CI: 1.39–1.89). Cesarean delivery was associated with substantially lower odds of EIBF (OR = 0.40; 95% CI: 0.33–0.49). Compared with home deliveries, births in government facilities (OR = 0.58; 95% CI: 0.47–0.71) and private/NGO facilities (OR = 0.53; 95% CI: 0.42–0.66) were associated with reduced likelihood of EIBF. Significant regional variation in EIBF was observed across administrative divisions. Maternal age, education, and household wealth index were not consistently associated with EIBF after adjustment. Based on the univariate analysis, the prevalence of EIBF among mothers in Bangladesh is 63.3%. The 95% Confidence Interval for this prevalence is (61.9% – 64.7%). Conclusion The significance of skin-to-skin contact for EIBF in Bangladesh is demonstrated in this study. The results indicate the necessity of focused initiatives to support EIBF, especially in medical settings and after cesarean deliveries. To understand the geographical differences in EIBF rates and create strategies to deal with them, more investigation is required. These discoveries can influence practice and policy to raise EIBF rates among Bangladesh’s varied demographics, improving the health of mothers and their offspring in the process.